2020
DOI: 10.1084/jem.20191913
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of endogenous nucleic acids by ZBP1 induces keratinocyte necroptosis and skin inflammation

Abstract: Aberrant detection of endogenous nucleic acids by the immune system can cause inflammatory disease. The scaffold function of the signaling kinase RIPK1 limits spontaneous activation of the nucleic acid sensor ZBP1. Consequently, loss of RIPK1 in keratinocytes induces ZBP1-dependent necroptosis and skin inflammation. Whether nucleic acid sensing is required to activate ZBP1 in RIPK1-deficient conditions and which immune pathways are associated with skin disease remained open questions. Using knock-in mice with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 63 publications
0
75
1
Order By: Relevance
“…Transcriptomes of ZBP1-depleted myeloma cells driven by distinct primary oncogenes, One of the physiological roles of ZBP1 is to prevent or promote programmed cell death and inflammation through interaction with RIPK1 or RIPK3 respectively in response to pathogen or cellular dsRNA 4,5,7 . Alternatively, ZBP1 has been linked with activation of the IFN type I pathway via TBK1 phosphorylation of IRF3, with the latter directly activating amongst others the IFN genes themselves and ISG15, a hallmark IFN type I response gene 1,2,43 . However, such ZBP1-IRF3 interactions have only been shown in an exogenous system 1,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomes of ZBP1-depleted myeloma cells driven by distinct primary oncogenes, One of the physiological roles of ZBP1 is to prevent or promote programmed cell death and inflammation through interaction with RIPK1 or RIPK3 respectively in response to pathogen or cellular dsRNA 4,5,7 . Alternatively, ZBP1 has been linked with activation of the IFN type I pathway via TBK1 phosphorylation of IRF3, with the latter directly activating amongst others the IFN genes themselves and ISG15, a hallmark IFN type I response gene 1,2,43 . However, such ZBP1-IRF3 interactions have only been shown in an exogenous system 1,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Discovery of these dynamics uncovered a previously unknown homeostatic regulatory function for RIPK1 in restricting endogenous, spontaneous ZBP1 activation. Several groups have recently explored how ZBP1 is activated in sterile conditions and proposed that Z-RNA acts as the ligand to activate ZBP1-mediated cell death and inflammation (Devos et al, 2020;Jiao et al, 2020;Kesavardhana et al, 2020;Wang et al, 2020). Understanding this pathway is essential to unlock key mechanisms, perhaps the sensing of Z-NAs, that prime skin inflammation and autoinflammatory diseases and identify specific signaling cascades for therapeutic targeting.…”
mentioning
confidence: 99%
“…Understanding this pathway is essential to unlock key mechanisms, perhaps the sensing of Z-NAs, that prime skin inflammation and autoinflammatory diseases and identify specific signaling cascades for therapeutic targeting. Devos et al (2020) and other recent studies have identified that endogenous nucleic acid sensing is critical for ZBP1 activation to induce necroptosis, skin and colon inflammation, and perinatal lethality (Jiao et al, 2020;Kesavardhana et al, 2020;Wang et al, 2020). To understand ZBP1 activation mechanisms, Devos et al (2020) crossed Ripk1 EKO mice with ZBP1 knock-in mice, which contain mutations disrupting the nucleic acid binding of the ZBP1 Zα domains (N46A, Y50A, N122A, Y126A; Maelfait et al, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations